2020
DOI: 10.3390/toxins12040238
|View full text |Cite
|
Sign up to set email alerts
|

PGN and LTA from Staphylococcus aureus Induced Inflammation and Decreased Lactation through Regulating DNA Methylation and Histone H3 Acetylation in Bovine Mammary Epithelial Cells

Abstract: Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) are the most common pathogens of mastitis, and S. aureus generally causes subclinical mastitis which is more persistent and resistant to treatment. Peptidoglycan (PGN) and lipoteichoic acid (LTA) are cell wall components of S. aureus. Although the roles of PGN and LTA in causing inflammation are well studied, the epigenetic mechanisms of the effects of PGN and LTA on the inflammation and lactation remain poorly understood. This study characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…Additionally, abnormal expression of IL6 was revealed to be due to altered DNA methylation rather than genetic mutation during clinical mastitis (Zhang et al, 2018). Moreover, methylation changes in NCKAP5 and transposon MTD were associated with the development of S. aureus mastitis (Wang et al, 2020), while hypomethylation of global DNA methylation induced by S. aureus infection repressed DNA methyltransferase activity in bovine mammary epithelial cells (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, abnormal expression of IL6 was revealed to be due to altered DNA methylation rather than genetic mutation during clinical mastitis (Zhang et al, 2018). Moreover, methylation changes in NCKAP5 and transposon MTD were associated with the development of S. aureus mastitis (Wang et al, 2020), while hypomethylation of global DNA methylation induced by S. aureus infection repressed DNA methyltransferase activity in bovine mammary epithelial cells (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Other studies have also shown that LTA and PGN could cause the DNA hypomethylation of the key regulators of inflammatory pathways, promoting the release of a variety of inflammatory factors [37,38]. In addition, our previous studies showed that LPS, LTA, and PGN suppressed the expression of lactation-related genes of BMECs due to reducing histone H3 acetylation through regulating HAT and HDAC activity [19,39]. Thus, we speculated that co-stimulation with LPS, LTA, and PGN might have an additive effect on DNA hypomethylation and histone hypoacetylation, producing a more intense inflammatory response and decreasing casein expression to a greater degree than single stimulation of either of the PAMPs in BMECs.…”
Section: Introductionmentioning
confidence: 78%
“…LPS could cause DNA hypomethylation at many inflammatory loci by suppressing DNMT expression, and then increase the inflammatory factor expression of human dental pulp cells [32] and macrophages [33], rat brain tissue [34], bovine fibroblasts [35], and so on. Our previous study showed that LPS, LTA, and PGN enhanced the inflammatory responses of BMECs by decreasing DNA methylation levels [19,36]. Other studies have also shown that LTA and PGN could cause the DNA hypomethylation of the key regulators of inflammatory pathways, promoting the release of a variety of inflammatory factors [37,38].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations